Uniform convergence of the Fourier-Laplace series - Rasedee, Ahmad Fadly Nurullah; Rakhimov, Abdumalik; Akhmedov, Anvarjon (American Institute of Physics, 2017)
This study examines the problem of uniform convergence for the functions from the Nikolskii class. The uniform convergences for the Riesz means of the Fourier-Laplace series in the Nikolskii class Hpa(SN) proved under certain conditions.